Introducing Kyla May Miss.Behaves - May, Kyla (New York, 2005)
Kyla May writes in her journal about her life, her family, and her many daydreams, which repeatedly get her in trouble at the Melbourne, Australia creative arts school she attends.
Keywords: Imagination; Fiction; Schools; Fiction; Diaries; Fiction; Australia; Fiction